FRI0265 Cytokines and correlations with patient reported outcomes in systemic lupus erythematosus and population controls. (15th June 2017) - Pettersson, S; Idborg, H; Eketjäll, S; Gunnarsson, I; Svenungsson, E
Abstract : Background: In open questions patients with systemic lupus erythematosus (SLE) report fatigue as the most distressing symptom. Pro-inflammatory cytokines are generally suggested to contribute to fatigue in chronic diseases, however results are contradictory (1, 2). Patient reported outcome measures (PROMs) quantify patients' experiences of qualities like fatigue and depression, which have great impact on both physical and psychological wellbeing. If PROMs are associated with pro-inflammatory cytokine activity in SLE has not yet been well investigated Objectives: In this study we explored the relationship between a large set of cytokines and self-assessments of fatigue, anxiety, depression and quality of life in a large group of patients with SLE and in matched controls. Methods: In a cross-sectional setting, persons with SLE and age- and gender-matched population controls responded to PROMs, assessing fatigue (Multidimensional Assessment of fatigue Scale), depression/anxiety (Hospital Anxiety and Depression Scale) and health related quality of life (Medical Short Form 36 (SF-36)). 30 cytokines were analyzed (MSD 30-plex cytokine assay). Spearman's rank correlation coefficient (rs ) between cytokines and PROMs were calculated. Results: 423 patients, age 46.6 (±15.3) and 315 controls age 47.5 (±14.6) (p 0.43) were included. Of 30 analyzed cytokines 20 gave reliable results and were correlated to PROMs. Five of the cytokines (IL-6, TNF-alfa, IL-15, MCP-1 and MIP-1-beta) correlated best (rs ≥0.37) with investigated PROMs (table 1 ). Fatigue correlated with TNF-α (rs =0.32), IL-15 (rs =0.31), and MIP-1-beta (rs =0.32), p<0.01 for all. When summarizing SF-36 results we noted a pattern of stronger correlations between investigated cytokines and the physical component than the mental component. Anxiety and depression correlated, but weakly (rs <0.25). Conclusions: Most PROMs were positively associated with pro-inflammatory cytokines. Fatigue and PROMs reflecting physical aspect of disease correlated most convincingly, while correlations with mental aspects were weaker. References: Omdal R, et al (2002). Fatigue in patients with systemic lupus erythematosus: lack of associations to serum cytokines, antiphospholipid antibodies, or other disease characteristics. J Rheumatol. Roerink ME et al (2017). Interleukin-1 as a mediator of fatigue in disease: a narrative review. J Neuroinflammation. Disclosure of Interest: None declared